Barriers to Utilization of Postnatal Care Services: Mothers and Health Providers Perspective - Shrestha, Jene; Yadav, Dipendra Kumar (Journal of Nepal Health Research Council, 2021)
Background: Access to and utilization of post-natal care services is a major challenge as the majority of maternal deaths occur during post-natal period. Although geographical factors and access to health facilities in urban area are feasible as compared to rural area the utilization of all three postnatal visits remains low. Hence, this study aims to explore the barriers in utilization of postnatal care services by mothers from the perspective of mother’s and health service providers as well. Methods: A qualitative study was done using community- based exploratory design in urban area of Kathmandu district. In-depth interview with mothers with infants above 45 days to 1 year of age and key informant interviews with health care providers were done using interview guidelines. Thematic analysis was done.Results: Seven themes emerged through thematic analysis, which were further classified into category and sub categories. Poor recording and reporting system, poor health communication, postnatal care visits less prioritized among maternal health services, prerequisites to construction, and postnatal care services/information dependent on female community health volunteer, less utilization of mass media, and perception of people were identified as barrier for utilization of postnatal services.Conclusions: The common reason for non-utilization of postnatal care service is identified as poor health communication that resulted in lack of knowledge on the benefit and timing of postnatal care. Lack of awareness among women on postnatal care services shows lack of effort in making postnatal care related information easily available and accessible. Hence, education and awareness on postnatal care services along with proper therapeutic communication is seen essential to complete the continuum of care in maternal health services.Keywords: Barriers; health Personnel; non- utilization; postnatal care; qualitative